Hospital discharge planning as a continuity care strategy for primary care (Research, Society and Development, 2020)
Objective: to analyze hospital discharge planning as a strategy of continuity of care for Primary Health Care. Method: qualitative study, carried out in a university hospital in the southern region of the country. Online questionnaire applied with Nurses and interview with the Director of Nursing, between October and November 2019 and Content Analysis to analyze the data collected. Results: Nurses conducted interviews and clinical assessment of patients during hospitalization and for planning discharge from hospital. In preparing for hospital discharge, several professionals were involved, mainly doctors and nurses, however, there was no counter-referral protocol, with the summary of medical and nursing discharges for the continuity of care for Primary Health Care. The Nurses guided the family about home care, assessed socioeconomic conditions and the home environment. Conclusion: the use of protocols at hospital discharge allows nurses to follow planned care and promote continuity of care for Primary Care.